Short-term professional training in a computer assembly mini-course at the Federal Institute of Pará, Marajó Island (Research, Society and Development, 2021)
This paper aims to demonstrate the importance of computer assembly through mini-course, a practical and efficient alternative for the construction of computer concepts, to evaluate the relevance of the course for the training, qualification and work perspective for the participants. Two different target audiences were compared: the first, students of the Federal Educational Institution, and the second, members of the external society A 'I School of Vacations, held by the Federal Institute of Education, Science and Technology of Pará - Campus Breves, with the objective of applying alternative methods of practical teaching. Thus, it was held from 03 to 07 July 2017, with the participation of 21 students, being servants, students of the Technical Course in Integrated Computer Science to High School with duration of 20 hours, the Mini-Course - Computer Assembly. In this sense, it is necessary to make an analysis of the teaching and learning process developed in the mini-course, as well as the perspectives of the impact of this mini-course for the training of the participant for the labor market, taking into account the current historical moment of information technology that we live. This paper presents the results obtained from the evaluation of the mini-course, carried out through the application of a questionnaire.